6m+7=49*

Simple and best practice solution for 6m+7=49* equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m+7=49* equation:



6m+7=49*
We move all terms to the left:
6m+7-(49*)=0
We add all the numbers together, and all the variables
6m+7-0=0
We add all the numbers together, and all the variables
6m+7=0
We move all terms containing m to the left, all other terms to the right
6m=-7
m=-7/6
m=-1+1/6

You can always share this solution

See similar equations:

| 3.8+4.5x-1.4=8.5 | | 0.25/3=x/11/3 | | -685+m/4=-11 | | 2x=40-12 | | 17x-6=7x-6 | | (X+4)+(3x-7)=(x-2)+(3x+8) | | 7x+x+8=56 | | x+2x+4x=?7x | | 7x^2+86x+399=0 | | (9?x)?(2?x)=7 | | 9?x?2?x=7 | | .3x+.5x(50-x)=18 | | 49x+2=0 | | -6x+-55=1 | | -6x+(-55)=1 | | -6x-20=70 | | 15x^2-46+16=0 | | (3a-2)(5a-4)=(3a-2) | | 2(-1)-9y=-25 | | n+5-1=-1 | | n+5?1=?1 | | 2(5c+2)-2c=3(2c=3)=7 | | 5^2x+5=12^x | | 5(2y-1)-4(y-3)=20 | | 1^x=5x+2 | | -3(4p-2)=2(p-1) | | 4(x-1)+4x-1=4 | | (w-7)(w-9)=0 | | 5(9-4x)=40 | | 3(5x-7)=4 | | 3u+1=u+8 | | 2u+8=4+u |

Equations solver categories